EVALUATION OF ENTERPRISE HUMAN RESOURCES: THE THEORY BACKGROUND - Olga Vlasenko; Mariia Sokolova (Izdevnieciba "Baltija Publishing", 2021)
This article is devoted to the peculiarities of human resources evaluation in enterprises. The human resources evaluation has a special place in human resource management, because it allows you to identify the actual situation in an enterprise, find disadvantages and weaknesses in management, so that you can provide recommendations basing on its results. The main purpose of the study was to develop the theoretical principles for assessing human resources, which should establish the level of quantitative and qualitative characteristics in the terms of determining the state of motivation and efficiency for human resources. In the study, the authors stressed on the cyclical nature of human resource management in an enterprise. At the same time, in their opinion, the human resources evaluation takes a special place because it makes all actions passing through the human resources management system. The authors also stressed on the impact of motivation upon an enterprise efficient operation, and including but not limiting to the human resources. They found that motivation has a special relevance for human resource management, and thus is gained by solving such problems as coordination, matching up of the needs and means, motives and goals of human resources and an enterprise as a whole, identification and resolution of emerging contradictions between these goals and needs of human resources and an enterprise. Solving these problems is possible after a comprehensive evaluation of an enterprise's human resources. The authors propose to conduct a comprehensive evaluation in clearly defined areas: quantitative and qualitative evaluation, evaluation of the motivational state of human resources, and the final stage is to evaluate the efficiency of using Enterprise Human Resources. In the result of such evaluation, the administrative goal of human resource management will be achieved due to adoption of sound administrative decisions; thus, the information goal will be achieved as well, which is that both employees and managers have the opportunity to obtain reliable information about the activities; of course, the motivational goal of evaluation itself is among the most important means of motivating people's behaviour. In the authors' opinion, their proposed theoretical approach to the evaluation of human resources, which is implemented due to identifying the level of quantitative and qualitative characteristics of human resources' motivation and efficiency, will lead to conscious human resource management.